FORMAÇÃO CONTINUADA E PESQUISA-AÇÃO CRÍTICA: DAS VONTADES INDIVIDUAIS AOS CONSENSOS PROVISÓRIOS - Soave, Alana Rangel Barreto (2021)
The present study aimed to analyze, through collaborative-critical action research, the process of collaboration between academic researchers and context researchers in the constitution of processes of continuous education of public managers in the city of Domingos Martins/ES through critical self-reflection. To this end, in general terms, it focused on the training demands in their contexts of action by the two managers of the Reference Center for Inclusive Education (CREI), as well as the dialogue about the training perspectives that emerged in the course of this researchtraining, knowing, identifying and reflecting on the training concepts that guide and support the practices of public managers of the Municipal Department of Education and Sports and the Research and Training Center, considering the planning of continuous training aimed at education professionals in the municipal school system from Domingos Martins/ES. In the course undertaken, there was a collaboration with the continuous training of public managers of Special Education at CREI and of education professionals working in the municipal network, through the constitution of study-reflection groups in a collaborative-critical perspective during the period of the pandemic. It was based on the critical social theory of Jürgen Habermas, with emphasis on the concepts of Communicative Action, Strategic Action, Technical Rationality and Communicative Rationality. As an epistemological and methodological perspective, collaborative-critical action research was adopted, as postulated by Carr and Kemmis , based on the principle of critical self-reflection. Two CREI managers, a university professor, an undergraduate student of the Pedagogy course and a master's student were elected as participant-subjects. The data production process was organized in two moments, namely: The approximation and understanding of the context and constitution of a partnership with the municipality and the collaboration processes: constitution of listening groups and study-reflection groups. Participant observation, discursive spaces, study-reflection groups and dialogues that took place in the group of a social message network were used as strategies for the production of data. The interpretation and analysis of the data took place in the light of Habermasian critical social theory, in addition to authors who study the training of education professionals in a critical-emancipatory perspective. The research pointed out the power of continuous education built from a critical perspective, as well as the relevance of investing in the teaching-research-extension triad of the University as a way of contributing to collaborative and formative processes for the school inclusion of the target audience of Special Education students. in ordinary schools. It also demonstrated the formative character of collaborative-critical action research for academic researchers and researchers in the context. As a product of this dissertation emerged the continuing education called ―Pedagogical planning in times of pandemic: implications for Special/Inclusive Education‖ for education professionals in the municipal school system, in the year 2020.